Pengaruh Edukasi Media Leaflet Terhadap Penggunaan Alat Pelindung Diri (APD) Pada Petugas Pengangkut Sampah Di UPT TPA Tamangapa Antang - Asriani, Cici; Baharuddin, Alfina; Ulmy Mahmud, Nur (Window of Public Health Journal, 2025)
Waste transportation is an activity that starts from the collection process and continues with the transportation of waste. The problem in this study is related to the influence of leaflet media education on waste collectors' knowledge, attitudes, and actions. This study aims to determine the effect of leaflet media education on waste collectors' knowledge, attitudes, and actions regarding using Personal Protective Equipment (PPE). This type of research is quantitative with a "Pre-Experiment" design, specifically a one-group pretest design. In this design, the group of waste collectors is tested on their knowledge and attitudes before the leaflet media education. Then, the same group is tested again after the education to see if there is any change. The sampling technique used a total sampling of 59 samples. The data in this study were obtained from filling out questionnaires and observations and then analyzed using the Mc. Nemar test at a 95% confidence level (α = 0.05). From the results of the study, it was found that there was a difference in the level of knowledge of waste collectors before being given education; namely, 27 (45.8%) had sufficient knowledge, and the level of knowledge of waste collectors after being given education was 51 (86.4%). The conclusion of this study is to determine the effect of leaflet media education on the knowledge of waste collectors at the Tamangapa Antang Landfill UPT regarding the use of Personal Protective Equipment (PPE) while working. It is recommended that waste collectors implement the use of Personal Protective Equipment (PPE) correctly and adequately so that poor knowledge can be improved.